2016
DOI: 10.1002/alr.21707
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for route of allergy immunotherapy: a comparison of four delivery methods

Abstract: SCIT earned the lowest mean rank and had the least number of participants rank it as the most preferred method. Among the other 3 choices, by mean scores, SLIT was preferred most compared to either AIT or OMIT; but when considering first choices only, there were no significant differences in preference. Most of the study participants identified the convenience of home IT administration as the most important factor in their ranking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…While an initial meta‐analysis reported that SCIT was more effective in symptom control and reduction in medication, a more recent study provided indirect evidence that SCIT and SLIT have a similar efficacy for the treatment of allergy . Patients have been reported to show a preference for SLIT over SCIT …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While an initial meta‐analysis reported that SCIT was more effective in symptom control and reduction in medication, a more recent study provided indirect evidence that SCIT and SLIT have a similar efficacy for the treatment of allergy . Patients have been reported to show a preference for SLIT over SCIT …”
Section: Introductionmentioning
confidence: 99%
“…6 Patients have been reported to show a preference for SLIT over SCIT. 15 The mechanism of action for successful specific immunotherapy, irrespective of administration route, is thought to involve induction of neutralizing antibodies, an increased activity of regulatory T cells characterized by IL-10 production, and a gradual decline in specific IgE. The mechanisms underlying clinical efficacy in either SCIT or SLIT and the exact differences between the two treatments are not fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that oral mucosal immunotherapy combined with adjuvants might represent a safer way to progress from SLIT to OIT, particularly in high-risk individuals [94 && ]. In a recent preference survey, individuals with chronic rhinitis undergoing allergy testing chose OMIT, SLIT, and AIT as their first choice with similar frequency, whereas SCIT had a significantly fewer number of first choices compared to the other three delivery methods [95].…”
Section: Oral Mucosal Immunotherapymentioning
confidence: 99%
“…However, patient preference for IT modality and their tendency for compliance with a specific modality remain frequent questions. Chester et al 15 evaluated patient preference for IT method in a prospective study of 228 patients scheduled for allergy testing. These authors found the highest preference for aqueous sublingual IT (SLIT), followed by allergy IT tablets, oral mucosal IT, and finally subcutaneous IT (SCIT).…”
mentioning
confidence: 99%
“…In a study of IT compliance, Leader et al 16 analyzed 274 SLIT and SCIT patients and noted significantly higher rates of excellent compliance at all stages of treatment with SCIT, as compared to SLIT. Considering the results of the Chester et al 15 and Leader et al 16 studies together, it is interesting to contemplate why SCIT, as the less preferred IT modality, has higher compliance rates. Could patient "investment" in the less desirable SCIT modality (ie, with respect to time, office visits, injection discomfort) make them more likely to be compliant with treatment?…”
mentioning
confidence: 99%